Magnetic artificial periosteum with micro-nano multilevel structure as well as preparation method and application of magnetic artificial periosteum
The magnetic bionic periosteum prepared through electrospinning technology and self-assembly method solves the shortcomings of the existing bionic periosteum in terms of mechanical properties and biological activity, and achieves efficient bone defect repair results, and has broad application prospects.
Patent Information
- Application Number
- CN202510658974.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-21
- Publication Date
- 2025-08-08
AI Technical Summary
The existing artificial bionic periosteum is difficult to meet the clinical repair needs in terms of mechanical properties and biological activity, and autologous bone grafts and allogeneic bone grafts have problems with insufficient donors and immune rejection.
Electrospinning technology is used to mix polycaprolactone, magnetic hydroxyapatite nanoparticles and Chinese herbal active ingredients, combined with polysaccharide polymer materials, and magnetic bionic periosteum with micro-nano multi-level structure is prepared through self-assembly and freeze-drying. The magnetic hydroxyapatite nanoparticles and external magnetic fields are used to promote bone repair.
The prepared magnetic bionic periosteum has excellent mechanical properties and biological activity, which can significantly promote cell adhesion, proliferation and bone defect repair, provide an ideal microenvironment and improve bone repair efficiency.
Smart Images

Figure CN120437376A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomedical material development, and in particular to a magnetic artificial periosteum with a micro-nano multi-level structure, and a preparation method and application thereof. Background Art
[0002] Bone defects caused by skeletal pathology or accidents can severely impact human quality of life. With the aging population, the number of bone defect cases continues to rise. Currently, bone grafts are commonly used clinically to repair critical-sized bone defects. However, autologous and allogeneic bone grafts are subject to issues such as limited donor availability, immune rejection, and ethical considerations. Bone tissue engineering scaffolds based on various biomaterials also suffer from weak osteogenic activity and suboptimal bone integration. The natural periosteum is a highly vascularized connective tissue membrane that covers virtually all cortical bone surfaces, except in joints. As a reservoir of growth factors and various bone cells, the periosteum provides growth factors and recruits osteoblasts to accelerate bone regeneration when a bone defect develops. However, when a critical-sized bone defect occurs, the natural periosteum attached to the cortical bone surface is likely to be damaged, disrupting the nutrient supply and bioactive factor supply to the bone tissue, severely impairing bone repair. Despite the crucial role of natural periosteum in bone regeneration, its donor supply is extremely limited, making it difficult to meet the needs of widespread clinical application. Therefore, the construction and application of artificial bionic periosteum has important research value in the repair of critical-sized bone defects. The construction of functional artificial periosteum through biomimetic design and advanced materials technology has the potential to not only replace some of the biological functions of natural periosteum but also promote the regeneration and reconstruction of bone tissue, thus possessing broad application prospects.
[0003] Natural bone tissue has a complex multi-level hierarchical structure from the nanoscale to the macroscale. This unique construction method not only gives it excellent mechanical strength, but also good biological properties. Bionic construction of materials with micro-nano multi-level structures can effectively simulate the microenvironment of natural bone tissue, promote cell recruitment, adhesion, proliferation and osteogenic differentiation, and thus significantly improve the regeneration and repair efficiency of bone tissue. However, existing artificial bionic periosteum mostly focuses on mimicking the macroscopic or hierarchical structure of natural periosteum, and still has certain limitations in mechanical properties and bioactivity, making it difficult to fully meet clinical repair needs. Summary of the Invention
[0004] The purpose of the present invention is to provide a magnetic artificial periosteum with a micro-nano multi-level structure and its preparation method and application, which has better mechanical properties and biological activity.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a magnetic bionic periosteum, comprising the following steps:
[0007] S1, mixing a polycaprolactone solution, magnetic hydroxyapatite nanoparticles and active ingredients of Chinese herbal medicine to obtain an electrospinning solution, and performing an electrospinning process to obtain an electrospinning membrane;
[0008] S2, mixing the electrospun membrane with an alkaline solution of a polysaccharide polymer material for 10 to 20 minutes, then transferring the mixture to an ethanol aqueous solution, mixing and contacting for 0.5 to 2 hours, to obtain a self-assembled product;
[0009] S3. freeze-drying the self-assembled product to obtain the magnetic bionic periosteum.
[0010] Preferably, the active ingredients of Chinese herbal medicine are selected from one or more of icariin, berberine, total flavonoids of Rhizoma Drynariae, tanshinone, psoralen or astragalus polysaccharide.
[0011] Preferably, the solute of the alkaline solution of polysaccharide polymer material is selected from one or more of cellulose, chitin, chitosan or sodium alginate.
[0012] Preferably, in S1, the solvent used for the polycaprolactone solution contains dichloromethane and dimethylformamide.
[0013] Preferably, the volume ratio of dichloromethane to dimethylformamide is 3 to 5:1;
[0014] The concentration of the polycaprolactone solution is 0.1-0.3 g / mL.
[0015] Preferably, in S1, the volume of the polycaprolactone solution, the mass of the magnetic hydroxyapatite nanoparticles and the mass ratio of the active ingredient of the Chinese herbal medicine is 10-20 mL: 0.2-0.4 g: 10-20 mg;
[0016] And / or, the mixing is accompanied by magnetic stirring, and the time of the magnetic stirring is 5 to 10 hours;
[0017] And / or, in the electrospinning process, the spinning voltage is 15-20 kV, and the flow rate of the syringe pump is 0.5-1 mL / h.
[0018] Preferably, in S2, the solvent used in the alkaline solution of the polysaccharide polymer material contains LiOH, KOH, urea and water;
[0019] The mass ratio of LiOH, KOH, urea and water is 4-5:6-8:7-9:75-85;
[0020] The mass fraction of the polysaccharide polymer material alkaline solution is 0.5-2%;
[0021] and / or, the temperature of the ethanol aqueous solution is -20°C to 5°C;
[0022] The volume percentage concentration of the ethanol aqueous solution is 70-90%.
[0023] Preferably, the magnetic hydroxyapatite nanoparticles are obtained by a preparation method comprising the following steps:
[0024] Fe3O4 nanoparticles are mixed with a CaCl2 aqueous solution, and then subjected to ultrasonic treatment and heat treatment in sequence to obtain a Fe3O4 nanoparticle dispersion;
[0025] The Fe3O4 nanoparticle dispersion was mixed with an (NH4)2HPO4 aqueous solution, and an NH3·H2O aqueous solution was added to adjust the pH to 9-11 to obtain magnetic hydroxyapatite nanoparticles;
[0026] The particle size of the Fe3O4 nanoparticles is 10 to 30 nm;
[0027] The volume ratio of the Fe3O4 nanoparticles to the CaCl2 aqueous solution is 1-1.5 g:80-120 mL;
[0028] The concentration of the CaCl2 aqueous solution is 1 to 3 g / mL;
[0029] The ultrasonic treatment time is 10 to 20 minutes;
[0030] The heat treatment temperature is 50-70°C;
[0031] The heat treatment time is 40 to 60 minutes;
[0032] The volume ratio of the CaCl2 aqueous solution to the (NH4)2HPO4 aqueous solution is 1:0.8-1.2;
[0033] The mass fraction of the NH3·H2O aqueous solution is 10-30%;
[0034] After obtaining the magnetic hydroxyapatite nanoparticles, the process further includes washing, drying and crushing.
[0035] The present invention also provides a magnetic bionic periosteum prepared by the preparation method.
[0036] The present invention also provides the use of the magnetic bionic periosteum in preparing bone defect repair materials.
[0037] Beneficial effects of the present invention:
[0038] This invention, through a carefully designed preparation process that cleverly integrates active ingredients from traditional Chinese medicine with an alkaline solution of a polysaccharide polymer, has successfully developed a biomimetic periosteum with a micro-nano hierarchical structure. This process is not only simple to operate, easy to control, and implement, but also exhibits excellent mechanical properties, endowing the product with superior biological activity. The invention also incorporates magnetic hydroxyapatite nanoparticles, enabling the biomimetic periosteum to synergize with an external magnetic field, exerting a magnetic bioeffect that significantly promotes bone defect repair and further enhances the overall efficacy of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 is the TEM image of magnetic hydroxyapatite;
[0040] Figure 2 is the XRD pattern of magnetic hydroxyapatite nanoparticles;
[0041] Figure 3 This is the scanning electron microscopy morphology of PCL-CS-MHNPs-ICA biomimetic periosteum;
[0042] Figure 4 FTIR infrared spectra of PCL, CS, and PCL-CS;
[0043] Figure 5 Stress-strain curves of PCL, PCL-CS, PCL-CS-MHNPs, and PCL-CS-MHNPs-ICA;
[0044] Figure 6 is the breaking strength of PCL, PCL-CS, PCL-CS-MHNPs, and PCL-CS-MHNPs-ICA;
[0045] Figure 7 is the elastic modulus of PCL, PCL-CS, PCL-CS-MHNPs, and PCL-CS-MHNPs-ICA;
[0046] Figure 8 is the hysteresis loop of PCL-CS-MHNPs-ICA biomimetic periosteum;
[0047] Figure 9 is the drug release curve of PCL-CS-MHNPs-ICA biomimetic periosteum;
[0048] Figure 10 The adhesion morphology of MC3T3-E1 cells on different fiber membranes after 3 days of culture;
[0049] Figure 11 The statistical graph of the spreading area of a single MC3T3-E1 cell on different fiber membranes after 3 days of culture;
[0050] Figure 12 The cell viability of MC3T3-E1 cells after 1, 3, and 5 days of culture;
[0051] Figure 13 Three-dimensional reconstruction images of the skull defect area of SD rats at 4 weeks after surgery, including: (a) CON, (b) PCL-CS-MHNPs-ICA, and (c) PCL-CS-MHNPs-ICA (SMF). DETAILED DESCRIPTION
[0052] The technical solutions provided by the present invention are described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0053] Example 1
[0054] 1. Preparation of magnetic hydroxyapatite nanoparticles (MHNPs)
[0055] Fe₃O₄ nanoparticles (1.16 g) with a diameter of 20 nm were dispersed in 100 mL of a CaCl₂ aqueous solution (1.85 g of CaCl₂), ultrasonicated for 15 minutes, and then stirred at 60°C for 50 minutes. Subsequently, 100 mL of an aqueous (NH₄)₂HPO₄ solution (1.32 g of solute) was slowly added, using a 20% NH₃·H₂O aqueous solution as a precipitant. The pH of the system was adjusted to 10 to allow hydroxyapatite to form under alkaline conditions. After the reaction system cooled to room temperature, the product was rinsed alternately with deionized water and ethanol, dried, and then ground into a powder to obtain magnetic hydroxyapatite nanoparticles.
[0056] 2. Preparation of Electrospinning Membranes
[0057] 3 g of polycaprolactone (PCL) solid particles were dissolved in a mixture of 12 mL of dichloromethane and 3 mL of dimethylformamide. 0.3 g of MHNPs and 15 mg of icariin (ICA) were added. After magnetic stirring for 8 hours, the electrospinning solution was transferred to a 5 mL syringe equipped with a 20G needle for electrospinning. The positive electrode of a high-voltage DC power supply was connected to the syringe needle, and the negative electrode was connected to one end of a flat receiver. The electrospun membrane collected by the receiver was placed in a fume hood and dried for one week to remove the organic solvent. This yielded a PCL-MHNPs-ICA electrospun membrane. During spinning, the distance between the receiver and the needle was 15 cm, the spinning voltage was 18 kV, and the syringe pump flow rate was 0.72 mL / h.
[0058] 3. Preparation of chitosan (CS) alkaline solution
[0059] A certain amount of chitosan (CS) powder was dispersed in an alkaline solvent prepared by mixing LiOH, KOH, urea, and pure water in a mass ratio of 4.5:7:8:80.5. The mixture was stirred for 5 minutes, frozen at -80°C, and then thawed at room temperature with stirring. The freeze-thaw process was repeated three times. Finally, the thawed solution was centrifuged at 7000 rpm / 4°C for 10 minutes to obtain a clear, transparent chitosan alkaline solution with a mass fraction of 1%.
[0060] 4. Construction of magnetic biomimetic periosteum with micro-nano multi-level structure
[0061] The electrospun membrane was immersed in 100 mL of the aforementioned CS alkaline solution for 15 minutes, then rinsed in deionized water for 15 minutes. The membrane was then immersed in 80% ethanol at 0°C for 1 hour to complete the self-assembly process. The sample was then washed three times with deionized water until the pH was neutral and freeze-dried to obtain the magnetic biomimetic periosteum PCL-CS-MHNPs-ICA with a hierarchical micro-nanostructure.
[0062] Example 2
[0063] 1. Preparation of magnetic hydroxyapatite nanoparticles (MHNPs)
[0064] Fe₃O₄ nanoparticles (1.16 g) with a diameter of 20 nm were dispersed in 100 mL of a CaCl₂ aqueous solution (1.85 g of CaCl₂), ultrasonicated for 15 minutes, and then stirred at 50°C for 60 minutes. Subsequently, 100 mL of an aqueous (NH₄)₂HPO₄ solution (1.32 g of solute) was slowly added, using a 20% NH₃·H₂O aqueous solution as a precipitant. The pH of the system was adjusted to 10 to allow hydroxyapatite to form under alkaline conditions. After the reaction system cooled to room temperature, the product was rinsed alternately with deionized water and ethanol, dried, and then ground into a powder to obtain magnetic hydroxyapatite nanoparticles.
[0065] 2. Preparation of Electrospinning Membranes
[0066] 3 g of polycaprolactone (PCL) solid particles were dissolved in a mixture of 12 mL of dichloromethane and 3 mL of dimethylformamide. 0.2 g of MHNPs and 15 mg of icariin (ICA) were added. After magnetic stirring for 8 hours, the electrospinning solution was transferred to a 5 mL syringe equipped with a 20G needle for electrospinning. The positive electrode of a high-voltage DC power supply was connected to the syringe needle, and the negative electrode was connected to one end of a flat receiver. The electrospun membrane collected by the receiver was placed in a fume hood and dried for one week to remove the organic solvent. This yielded a PCL-MHNPs-ICA electrospun membrane. During spinning, the distance between the receiver and the needle was 15 cm, the spinning voltage was 18 kV, and the syringe pump flow rate was 0.72 mL / h.
[0067] 3. Preparation of chitosan (CS) alkaline solution
[0068] A certain amount of chitosan (CS) powder was dispersed in an alkaline solvent prepared by mixing LiOH, KOH, urea, and pure water in a mass ratio of 4.5:7:8:80.5. The mixture was stirred for 5 minutes, frozen at -80°C, and then thawed at room temperature with stirring. The freeze-thaw process was repeated three times. Finally, the thawed solution was centrifuged at 7000 rpm / 4°C for 10 minutes to obtain a clear, transparent chitosan alkaline solution with a mass fraction of 1%.
[0069] 4. Construction of magnetic biomimetic periosteum with micro-nano multi-level structure
[0070] The electrospun membrane was immersed in 100 mL of the aforementioned CS alkaline solution for 15 minutes, then rinsed in deionized water for 15 minutes. The membrane was then immersed in 80% ethanol at 0°C for 1 hour to complete the self-assembly process. The sample was then washed three times with deionized water until the pH was neutral and freeze-dried to obtain the magnetic biomimetic periosteum PCL-CS-MHNPs-ICA with a hierarchical micro-nanostructure.
[0071] Example 3
[0072] 1. Preparation of magnetic hydroxyapatite nanoparticles (MHNPs)
[0073] Fe₃O₄ nanoparticles (1.16 g) with a diameter of 20 nm were dispersed in 100 mL of a CaCl₂ aqueous solution (1.85 g of CaCl₂), ultrasonicated for 15 minutes, and then stirred at 60°C for 50 minutes. Subsequently, 100 mL of an aqueous (NH₄)₂HPO₄ solution (1.32 g of solute) was slowly added, using a 20% NH₃·H₂O aqueous solution as a precipitant. The pH of the system was adjusted to 10 to allow hydroxyapatite to form under alkaline conditions. After the reaction system cooled to room temperature, the product was rinsed alternately with deionized water and ethanol, dried, and then ground into a powder to obtain magnetic hydroxyapatite nanoparticles.
[0074] 2. Preparation of Electrospinning Membranes
[0075] 3 g of polycaprolactone (PCL) solid particles were dissolved in a mixture of 12 mL of dichloromethane and 3 mL of dimethylformamide. 0.3 g of MHNPs and 15 mg of icariin (ICA) were added. After magnetic stirring for 8 hours, the electrospinning solution was transferred to a 5 mL syringe equipped with a 20G needle for electrospinning. The positive electrode of a high-voltage DC power supply was connected to the syringe needle, and the negative electrode was connected to one end of a flat receiver. The electrospun membrane collected by the receiver was placed in a fume hood and dried for one week to remove the organic solvent. This yielded a PCL-MHNPs-ICA electrospun membrane. During spinning, the distance between the receiver and the needle was 15 cm, the spinning voltage was 18 kV, and the syringe pump flow rate was 0.72 mL / h.
[0076] 3. Preparation of chitosan (CS) alkaline solution
[0077] A certain amount of chitosan (CS) powder was dispersed in an alkaline solvent prepared by mixing LiOH, KOH, urea, and pure water in a mass ratio of 4.5:7:8:80.5. The mixture was stirred for 5 minutes, frozen at -80°C, and then thawed at room temperature with stirring. The freeze-thaw process was repeated three times. Finally, the thawed solution was centrifuged at 7000 rpm / 4°C for 10 minutes to obtain a clear, transparent chitosan alkaline solution with a mass fraction of 1.5%.
[0078] 4. Construction of magnetic biomimetic periosteum with micro-nano multi-level structure
[0079] The electrospun membrane was immersed in 100 mL of the aforementioned CS alkaline solution for 20 minutes, then rinsed in deionized water for 20 minutes. The membrane was then immersed in 80% ethanol at 0°C for 1 hour to complete the self-assembly process. The sample was then washed three times with deionized water until the pH was neutral and freeze-dried to obtain the magnetic biomimetic periosteum PCL-CS-MHNPs-ICA with a hierarchical micro-nanostructure.
[0080] Experimental example
[0081] Based on the technical solution of Example 1, the following relevant performance characterization and evaluation were performed.
[0082] 1. The prepared magnetic hydroxyapatite nanoparticles were ultrasonically dispersed in ethanol, dropped onto a copper grid and dried, and finally placed in the sample chamber of a transmission electron microscope for observation and imaging. The voltage of the transmission electron microscope was kept stable at 200 kV. Figure 1 .
[0083] like Figure 1 As shown in the figure, MHNPs present a combination of needle-like and spherical substances. Among them, the spherical substances are Fe3O4 nanoparticles, and the nano-scale fine needle-like crystal substances are hydroxyapatite. Fe3O4 magnetic nanoparticles are evenly dispersed in the reaction system, while Ca 2+ PO4 3- Under alkaline conditions, it is deposited on the surface of Fe3O4 nanoparticles in the form of hydroxyapatite, and finally the Fe3O4 nanoparticles are wrapped in the middle by hydroxyapatite.
[0084] 2. X-ray diffractometer was used to characterize the crystal structure of magnetic hydroxyapatite nanoparticles. The scanning range was 10-80° and the scanning speed was set to 5° / min. Co target was used in the test. The results are shown in Figure 2. Figure 2 shown.
[0085] The XRD patterns of MHNPs reveal that the diffraction peaks of MHNPs correspond to those of both hydroxyapatite and Fe3O4 nanoparticles, indicating that the MHNPs prepared by the co-precipitation method are composed of a composite of hydroxyapatite and Fe3O4 nanoparticles.
[0086] 3. Use scanning electron microscope to observe the micromorphology of PCL-CS-MHNPs-ICA biomimetic periosteum. After gold sputtering, use conductive glue to stick the sample on the sample stage and put it into the electron microscope room to observe its morphology. The acceleration voltage is 10-15kV. The results are as follows: Figure 3 shown.
[0087] like Figure 3As shown in the figure, spider-web-like CS nanofibers are deposited on the PCL micron fibers and inside their pores, forming a micro-nano multi-level structure, which provides a suitable microenvironment for cell adhesion, growth, and proliferation.
[0088] 4. The sample was cut into 1×1 cm size and the electrospun fiber membrane sample was analyzed by infrared spectroscopy using total reflection method. The results are as follows: Figure 4 shown.
[0089] In the infrared absorption spectrum of PCL, 1743 cm -1 represents the stretching vibration of C=O, 1178cm -1 Represents the stretching vibration of CO, 2900 cm -1 and 2970cm -1 Represents CH stretching vibration. In the infrared absorption spectrum of CS, 2900cm -1 and 2950cm -1 represents CH stretching vibration, 3470 cm -1 Represents the stretching vibration of OH, 1616 cm -1 The NH bending vibration is represented by the IR spectrum of PCL-CS at 1616 cm -1 A new peak appears at , which is attributed to the bending vibration of NH in CS. This confirms the successful deposition of CS on PCL.
[0090] 5. Use an electronic universal material testing machine to characterize the mechanical properties of the sample. Cut the sample into strip films, use a digital thickness gauge to measure the thickness of each strip and record it before testing. Perform a tensile test at room temperature with a tensile speed of 5 mm / min to obtain stress-strain curves and tensile strength. Analyze its fracture strength and elastic modulus. The results are as follows: Figure 5 、 Figure 6 and Figure 7 shown.
[0091] The mechanical properties test results of different fiber membranes are as follows Figure 5 、 Figure 6 and Figure 7 As shown in the figure, the PCL fiber membrane has a tensile strength of approximately 5.0 MPa and an elastic modulus of approximately 8.6 MPa. After CS deposition, the PCL-CS fiber membrane has a tensile strength of approximately 6.3 MPa and an elastic modulus of approximately 12.0 MPa. The enhanced mechanical properties of the PCL-CS fiber membrane can be attributed to the establishment of a micro-nano hierarchical fiber structure and the hydrogen bonding interaction between PCL and CS.
[0092] The hysteresis loop of the sample was measured using a vibrating sample magnetometer. All curves were measured within the external magnetic field range of -10kOe and +10kOe. Figure 8 shown.
[0093] like Figure 8 As shown in the figure, the saturation magnetic induction of nano-Fe3O4, MHNPs, and PCL-CS-MHNPs-ICA fiber membranes are 75.31emu / g, 43.63emu / g, and 20.45emu / g, respectively. Similar to nano-Fe3O4 and MHNPs, the magnetization curve of PCL-CS-MHNPs-ICA fiber membrane at room temperature exhibits typical superparamagnetism. When a magnetic material is coated with a non-magnetic material, the expression of its magnetic properties is suppressed to a certain extent. Therefore, the saturation magnetic intensity of the PCL-CS-MHNPs-ICA fiber membrane is lower than that of Fe3O4MNPs and MHNPs.
[0094] 6. Cut the fiber membrane into small discs with a diameter of 2 cm, immerse them in 5 mL of PBS buffer, and gently shake them on a shaker at 37°C. On days 1, 2, 4, 7, 10, 14, and 21, measure the drug concentration in the PBS buffer using a microplate reader (detection wavelength of 270 nm) to determine the mass of drug released. The cumulative drug release ratio is (M is the mass of drug released, M0 is the total mass of drug contained in the fiber membrane):
[0095]
[0096] The results are as follows Figure 9 shown.
[0097] The release of ICA can be roughly divided into three phases: rapid release, steady release, and equilibrium release. As the fibrous membranes were immersed in PBS buffer for extended periods, ICA on the fiber surface was released first, while ICA within the fibers had to penetrate the fibers to be released. Consequently, the release rate in the later stages slowed down until it reached a steady state. Although the initial release rate of ICA was faster than the later stages, a significant burst of ICA release was avoided, preventing the toxic side effects of excessive ICA release in the initial stage. The release trends of ICA from PCL-CS-MHNPs-ICA fiber membranes at different concentrations were generally consistent, with final release rates of approximately 74%, 52%, and 44% for the 0.5%, 1%, and 5% concentration groups, respectively. The first three weeks after bone defect formation are crucial, as various stem cells migrate to the defect site, proliferate, and differentiate, leading to localized new bone regeneration and completing the initial stages of bone regeneration. Good repair during this phase lays a solid foundation for the subsequent development of new bone into hard bone. During this period, the drug release curve of PCL-CS-MHNPs-0.5% ICA fiber membrane showed a higher utilization rate of ICA.
[0098] 7. Place the fiber membrane spun on a 14 mm round glass slide into a 24-well plate. When the MC3T3-E1 cells are in good condition and sufficient in number, add 5 × 104 The cells were seeded on the sample surface at a density of 100 cells / well. The experimental group was divided into five groups, namely PCL, PCL-CS, PCL-CS-MHNPs, PCL-CS-MHNPs-ICA, and PCL-CS-MHNPs-ICA (SMF). Among them, the PCL-CS-MHNPs-ICA (SMF) group required placing a NdFeB strong magnetic circular magnet under the culture dish and adjusting the distance between the two to provide a static magnetic field of 15mT for the cells. After 3 days of culture, the cells were stained with fluorescein thiocyanate (FITC)-labeled phalloidin and DAPI, and the spreading area of MC3T3-E1 cells was quantitatively analyzed using ImageJ 1.8.0. The results are shown in Figure 2. Figure 10 、 11 shown.
[0099] like Figure 10 、 Figure 11 As shown in the figure, the number of MC3T3-E1 cells adhering to the PCL fiber membrane is small, with a thin morphology and small pseudopodia. The adhesion of MC3T3-E1 cells on the PCL-CS fiber membrane has improved, with good spreading. Most of them are spindle-shaped, and some cells have extended pseudopodia. The adhesion of MC3T3-E1 cells on PCL-CS-MHNPs, PCL-CS-MHNPs-ICA, and PCL-CS-MHNPs-ICA (SMF) fiber membranes is significantly better than that on the PCL fiber membrane. The number of cells is significantly greater, and the cells grow closely and adhere to each other. Most of the cell edges extend pseudopodia and grow in contact. The spreading area of a single MC3T3-E1 cell was quantitatively analyzed. The cell spreading area on the PCL membrane was 594μm2, while the spreading area on the PCL-CS membrane increased significantly to 1171μm 2 This is mainly attributed to the micro-nanofibrous structure constructed by PCL / CS, which mimics the natural ECM and effectively promotes cell adhesion and growth. Furthermore, the cell spreading area on the PCL-CS-MHNPs-ICA (SMF) membrane was significantly increased to 1610 μm 2 There was no statistically significant difference in spreading area between the PCL-CS and PCL-CS-MHNPs-ICA groups. It is speculated that in addition to the effect of the micro-nanofiber structure, the synergistic effect of MHNPs, ICA, and SMF also had a significant impact on cell adhesion and spreading.
[0100] 8. PCL, PCL-CS, PCL-CS-MHNPs, and PCL-CS-MHNPs-ICA were cut into 5 mm × 5 mm diameter squares and placed in a 48-well plate. The front and back sides were sterilized by UV irradiation for 2 h. 300 μL PBS was added to each well to moisten the materials for 24 h, and then the PBS was discarded. 1 × 10 4For MC3T3-E1 cells, the PCL-CS-MHNPs-ICA (SMF) group required placing a strong NdFeB circular magnet below the cell culture dish and adjusting the distance between the magnets to provide a 15 mT SMF to the cells. Cell viability was measured using a CCK-8 assay at 1, 3, and 5 days.
[0101] Before the assay, discard the original culture medium with a pipette, add 200 μL of culture medium containing 10% CCK-8 working solution to each well, transfer the well plate to a cell culture incubator and incubate for 1 hour, then pipette 100 μL of solution into each well of a 96-well plate, and measure the OD value of each well at 450 nm using a microplate reader.
[0102] Calculate cell viability (OD0 is the OD value of the blank well, OD1 is the OD value of the CON group):
[0103]
[0104] CCK8 results Figure 12 As shown in the results, the proliferation activity of MC3T3-E1 cells of PCL-CS fiber membrane with micro-nano hierarchical structure is significantly better than that of PCL fiber membrane. The addition of ICA and MHNPs can significantly promote cell activity, so that PCL-CS-MHNPs-ICA fiber membrane can effectively promote the proliferation of MC3T3-E1 cells, and it can produce more obvious effects under the synergy of SMF.
[0105] 9. Experimental Animals: Twelve SD rats (8 weeks old) were randomly divided into three groups, with four rats in each group: CON group, PCL-CS-MHNPs-ICA group, and PCL-CS-MHNPs-ICA (SMF) group. SMF was added by symmetrically attaching several magnets to the sides of a cage, creating a uniform magnetic field. The magnets were adjusted to achieve an SMF of 15 mT. The skin and fascia were incised to expose the skull. A 5 mm hole was drilled in the skull using a dental drill and then covered with a material. Four weeks after surgery, the SD rats were euthanized, their skull specimens were collected, and fixed in 4% paraformaldehyde for later use. Before scanning, the specimens were removed from the 4% paraformaldehyde and any residual paraformaldehyde was carefully wiped off the surface. The specimens were fixed using a Micro-CT holder and scanned to assess the repair of the skull defect in the SD rats.
[0106] like Figure 13 ,like Figure 4-7 Shown are three-dimensional reconstructions of skull defects in SD rats. Four weeks after surgery, only a very small amount of bone tissue was formed in the CON group. The degree of bone regeneration in the experimental group was significantly greater than that in the CON group.
[0107] As can be seen from the above examples, the present invention provides a magnetic biomimetic periosteum with a micro-nano multi-level structure. The preparation method is scientific and efficient. Through electrospinning technology and self-assembly process, magnetic hydroxyapatite nanoparticles (MHNPs) and icariin (ICA) are successfully integrated into the PCL-CS fiber membrane. This biomimetic periosteum not only has good mechanical properties and magnetic responsiveness, but also can achieve sustained release of ICA, providing an ideal microenvironment for bone defect repair. Experimental results show that the PCL-CS-MHNPs-ICA fiber membrane significantly promotes the adhesion and proliferation of MC3T3-E1 cells, especially under the synergistic effect of a static magnetic field (SMF). The effect is more significant. This invention provides a new and efficient biomaterial for the field of bone repair with broad application prospects.
[0108] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A method for preparing a magnetic bionic periosteum, characterized in that: The following steps are involved: S1, mixing a polycaprolactone solution, magnetic hydroxyapatite nanoparticles and active ingredients of Chinese herbal medicine to obtain an electrospinning solution, and performing an electrospinning process to obtain an electrospinning membrane; S2, mixing the electrospun membrane with an alkaline solution of a polysaccharide polymer material for 10 to 20 minutes, then transferring the mixture to an ethanol aqueous solution, mixing and contacting for 0.5 to 2 hours, to obtain a self-assembled product; S3. freeze-drying the self-assembled product to obtain the magnetic bionic periosteum.
2. The preparation method according to claim 1, characterized in that The active ingredients of the Chinese herbal medicine are selected from one or more of icariin, berberine, total flavonoids of Rhizoma Drynariae, tanshinone, psoralen or astragalus polysaccharide.
3. The preparation method according to claim 1, characterized in that The solute of the alkaline solution of polysaccharide polymer material is selected from one or more of cellulose, chitin, chitosan or sodium alginate.
4. The preparation method according to claim 1, characterized in that In S1, the solvent used for the polycaprolactone solution contains dichloromethane and dimethylformamide.
5. The preparation method according to claim 4, characterized in that The volume ratio of dichloromethane to dimethylformamide is 3 to 5:1; The concentration of the polycaprolactone solution is 0.1-0.3 g / mL.
6. The preparation method according to claim 1, characterized in that In S1, the volume of the polycaprolactone solution, the mass of the magnetic hydroxyapatite nanoparticles, and the mass ratio of the active ingredient of the Chinese herbal medicine are 10-20 mL: 0.2-0.4 g: 10-20 mg; And / or, the mixing is accompanied by magnetic stirring, and the time of the magnetic stirring is 5 to 10 hours; And / or, in the electrospinning process, the spinning voltage is 15-20 kV, and the flow rate of the syringe pump is 0.5-1 mL / h.
7. The preparation method according to claim 1, characterized in that In S2, the solvent used in the alkaline solution of the polysaccharide polymer material contains LiOH, KOH, urea and water; The mass ratio of LiOH, KOH, urea and water is 4-5:6-8:7-9:75-85; The mass fraction of the polysaccharide polymer material alkaline solution is 0.5-2%; and / or, the temperature of the ethanol aqueous solution is -20°C to 5°C; The volume percentage concentration of the ethanol aqueous solution is 70-90%.
8. The preparation method according to claim 1, characterized in that The magnetic hydroxyapatite nanoparticles are obtained by a preparation method comprising the following steps: Fe3O4 nanoparticles are mixed with a CaCl2 aqueous solution, and then subjected to ultrasonic treatment and heat treatment in sequence to obtain a Fe3O4 nanoparticle dispersion; The Fe3O4 nanoparticle dispersion was mixed with an (NH4)2HPO4 aqueous solution, and an NH3·H2O aqueous solution was added to adjust the pH to 9-11 to obtain magnetic hydroxyapatite nanoparticles; The particle size of the Fe3O4 nanoparticles is 10 to 30 nm; The volume ratio of the Fe3O4 nanoparticles to the CaCl2 aqueous solution is 1-1.5 g:80-120 mL; The concentration of the CaCl2 aqueous solution is 1 to 3 g / mL; The ultrasonic treatment time is 10 to 20 minutes; The heat treatment temperature is 50-70°C; The heat treatment time is 40 to 60 minutes; The volume ratio of the CaCl2 aqueous solution to the (NH4)2HPO4 aqueous solution is 1:0.8-1.2; The mass fraction of the NH3·H2O aqueous solution is 10-30%; After obtaining the magnetic hydroxyapatite nanoparticles, the process further includes washing, drying and crushing.
9. The magnetic bionic periosteum prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the magnetic bionic periosteum according to claim 9 in preparing bone defect repair materials.